Parental Treatment Satisfaction Scores in a Day Care Pediatric Surgical Procedures - Sohail, Hamza; Tahir Shahzad Nawaz Babar,; Sarwar, Erum; Faryal Sadaqat,; Muhammad Asjad Saleem,; Hammad Ahmad Butt, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the mean Parental treatment satisfaction scores in a day care pediatric surgical procedure. Method: A cross-sectional study was conducted at the department of Pediatric Surgery, Liaquat National Hospital, Karachi between September 2019 to March 2020. All children of age 1-15 years of either gender admitted in Day Care Surgery for undergoing any of the pediatric surgical procedures (Hernia surgery, circumcision surgery or cysts surgery) were included. Data regarding age of child, gender, educational status of mother and father and parental age was obtained and was noted. The questionnaire covered the following areas: surgical staff and general treatment satisfaction, nursing staff and general information satisfaction; and Anesthetic staff satisfaction. The total parenteral treatment satisfaction scores were calculated. Results: Age range of children in this study was from 1 to 15 years with mean age of 7.7 ± 5.5 years, mean age of mother was 35.1 ± 7.5, mean age of father was 39.7 ± 6.9, mean duration of surgery was 45 ± 13 and mean duration of anesthesia was 47 ± 5 in minutes. The mean Parental treatment satisfaction scores in a day care pediatric surgical procedure was 6.67 + 0.7. Conclusion: The satisfaction level of the parents was fair enough considering the units where pediatric sedation was administered. When the physical conditions and the communication with patients and their relatives are improved and the procedure schedule is followed strictly, there will be further improvement in positive clinical results.